EVALUASI DAN OPTIMALISASI PERENCANAAN PAJAK DALAM RANGKA UNTUK MEMINIMALKAN PEMBAYARAN PAJAK PENGHASILAN BADAN (PPh) PADA PT “MKJ” DI SIDOARJO TAHUN 2015 - Miftha Kartika Juliansyah; Hari Hananto (CALYPTRA, 2018)
The purpose of this study is to describe how the implementation of the right tax planning to tax savings, especially in this research are discussed regarding Income Tax (PPh) Agency. During this time there were already efforts made by PT “MKJ” to do tax planning but not optimal due to the limitations of his knowledge of tax planning. In the application of the tax planning should be analyzed first what kind of taxation issues facing the company in order for the implementation in the application of the tax planning goes well. This study is included within a qualitative study which is an applied research, which will provide solutions regarding the proper application of tax planning so that can help PT “MKJ” to minimize the taxes that must be paid. In this study uses data from the PT “MKJ”. In optimizing the implementation of tax planning, there is a strategy that can be done by PT "MKJ". The strategy is to maximize the deductible costs by creating a nominative list of entertainment expenses, promotional costs, and transportation expenses, the use of gross up method for employee health costs, donation expenses of no more than 5% of net profit referring to Ministerial Regulation Finance, and other strategies. This tax planning can result in savings on the tax burden of PT "MKJ" of IDR 15.130.694. With this tax savings is expected to be useful in the future for PT "MKJ".